Is Preemptive Analgesia with Pregabalin effective in Total Knee Replacement? A Prospective Study - Mariappan, Selvamari; Kumar, Satish; Kumar, Ashok (Journal of Neonatal Surgery, 2025)
Introduction: The aim of the study is to assess the effectiveness of preemptive analgesia with Pregabalin In controlling Post Operative pain. Materials and Methods: A total number of 50 Patients who had moderate to severe OA knee who wanted to get Total Knee Replacement were included In the study. Inclusion Criteria includes Moderate to Severe OA Knee, Moderate to Severe deformity. Exclusion Criteria includes Patient who had Uncontrolled Diabetes, allergy/ intolerance to drug. 50 patients were randomly allocated into two groups namely Group A ( Pregabalin) and Group B ( Placebo). Group A received 150mg of Pregabalin one hour before the surgery and Group B received Placebo. Pain assessment was done using VAS scale at six hours, one day and one week after surgery. Results: At six hours Post OP, Mean VAS Score was 2.04±1.09 for Group A and 4.80±1.02 for Group B which indicates Pregabalin group had significant reduction of pain after surgery. The pain scale between the groups one day after surgery was 3.12 ±1.33 for Group A and 5.40 ±1.29 for group B. There was a significant decrease in pain score in Group A ( Pregabalin) than in Group B. Figure 3 represents the pain scale between the groups after one week of surgery. Mean VAS for Group A was 6.96 ±1.05 and 7.86 ±0.93 for Group B. There was no significant decrease of pain after one week of surgery.